The Bystander Effect of Trekking Tourism: Proposing a Typology of Environmental Ideal Types - Jensen, Martin Trandberg (Nepal Tourism and Development Review, 2013)
Tourism impacts in fragile nature-based environments have repeatedly been investigated from a wide array of academic viewpoints. However, in order to improve future researches that aim at measuring and/or elaborating on the pro-environmental awareness and behavioral patterns of trekking tourists, it is of utmost importance to identify the present environmental ideal types of trekkers. This research sets out to create an environmental typology of international trekkers visiting the Annapurna Conservation Area in Nepal. This research was conducted in between February-August, 2010, and included an extensive three-month ethnographic fieldwork within the conservation area, applying quantitative and qualitative techniques in order to create a framework of environmental trekking rationalities. A preliminary comparative analysis shows that trekkers seem to perceive themselves as more pro-environmental when trekking in Nepal compared to when at home. There appears to be a ‘selective optimistic self-perception’ among trekking tourists that creates a discrepancy between environmental self-perception and actual behavior. This research argues that trekkers seem to be locked into unsustainable consumption patterns, characterized by the constant strive toward Western comforts and commodities. In order to illustrate this case, the following article presents a novel typology that defines a number of different environmental ideal types within trekking. DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7369 Nepal Tourism and Development Review Vol.1(1) 2011 41-55